(untitled) (Palíndromo, 2019)
The purpose of this article is to think how dandyism can be understood as a manifestation of the artist’s autofiction. We intend to analyze the duplication of being as an expression of the melancholic mood and symptom of the genius of exception in modernity. It is intended to present as a transfiguration of work in an intermittent cycle of self-destruction and self-creation, in question the finitude of life and the infinity of art.